The mermaid's purse - Polacco, Patricia (New York : G.P. Putnam's Sons, an imprint of Penguin Group (USA), 2016)
"Stella loves books so much, she starts her own library--but then a storm threatens to destroy everything"--
Keywords: Books and reading -- Fiction; Libraries -- Fiction; Community life -- Michigan -- Fiction; Storms -- Fiction; JUVENILE FICTION / Books & Libraries; JUVENILE FICTION / Nature & the Natural World / Weather; JUVENILE FICTION / Social Issues / Friendship; Michigan -- History -- 19th century -- Fiction